Fright Night - Holland, Tom.; Amanda, Bearse; Dorothy Fielding; Jonathan Stark; Roddy McDowall; Stephen Geoffreys; William Ragsdale; Chris Sarandon (USA Columbia Pictures Corporation, 1985)
For young Charlie Brewster, nothing could be better than an old horror movie late at night. Two men move in next door, and for Charlie with his horror movie experience, there can be no doubt that their strange behavior is explained by the fact that they are a vampire and his undead day guardian. The only one who can help him hunt them down is a washed-up actor, Peter Vincent, who hosts Charlie's favorite TV show, Fright Night. Vincent doesn't really believe that vampires exist, but does it for the money...
When a teenager learns that his next door neighbour is a vampire, no one will believe him.
Tom Holland
Language: English Subtitles: English, Turkish
Keywords: Horror; Thriller; Comedy